A Comparative Study Between English And Indonesian Translation Shift In Cell Phone Gsm And Ruim Card Manual Books - Yuwana, Nia (2012)
This research belongs to descriptive qualitative research. The Data are words or phrases taken from the cell phone manual books which are included into the meaning shift. The data sources are from Mentari, IM3, Simpati, Fren, Esia, SIM Card manual book. This research is aimed at describing how the English translation shift formed in GSM/RUIM card manual books using semantics approach. There are two problem statements in this research. 1) What are the kinds of English and Indonesian translation shift used in GSM and RUIM card manual book?, and 2) What are the inaccurate forms of translation shift of the English and Indonesian occurred in GSM and RUIM card manual books? The research shows that: 1) There are two kinds of Indonesian and English translation shift used in GSM and RUIM card manual books, they are: unit shift and intra-system shift. From 30 data of the GSM/RUIM card manual books, there are 8 (eight) data or 26,7% containing unit shift and 22 (twenty two)data or 73,3% containing intra-system shift. So, it can be concluded that most data shift to similar part of speech (verb-verb, noun-noun, noun phrase-noun-phrase), but different in meaning. 2) There are two inaccurate forms of translation that shift in Indonesian and English occured in GSM and RUIM card manual books,they are: Explist meaning and Text meaning. From 30 data of the GSM/RUIM card manual books, there are 8 (eight) data or 26,7% that contain explicit forms of meaning and 22 (twenty two) data or 73,3% containing text meaning forms. So, it can be concluded that most data meaning forms relate to the text meaning. It is because the equivalence words or phrases in TL or Indonesian language should be appropriate from SL or English language.